Heated Tobacco Product Awareness, Use, and Perceptions in a Sample of Young Adults in the United States. Issue 11 (1st April 2021) - Berg, Carla J; Romm, Katelyn F; Patterson, Brooke; Wysota, Christina N
Abstract: Introduction: The emergence of heated tobacco products (HTPs) in the US marks a critical time for identifying those most likely to use, particularly among young adults. Aims and Methods: We analyzed Fall 2019 data from a longitudinal study of young adults (ages 18–34; n = 2375, Mage =24.66±4.68) in 6 US cities, 24.1% of whom used cigarettes and 32.7% e-cigarettes. We assessed HTP awareness, use, and sources, as well as perceived risk, social acceptability, and the likelihood of future use. Results: In this sample, 9.7% ( n = 230) heard of HTPs, 3.5% ( n = 84) ever used them, and 2.4% ( n = 56) reported past-year purchases (tobacco shops, 66.1%; traditional retailers, 60.7%; online, 39.3%; IQOS specialty stores, 35.7%). In multivariable analyses, having heard of HTPs correlated with being an older, male, and current cigarette and e-cigarette users; among those ever hearing of them, using HTPs correlated with being non-Hispanic and current cigarette and e-cigarette users. Greater likelihood of future use correlated with being older, male, sexual minority, non-Hispanic, and current cigarette and e-cigarette users. Among past-month users ( n = 78), the average number of days used was 5.48 (SD = 5.54). Past-month cigarette and e-cigarette users, respectively, who tried HTPs were more likely to report consistent or more frequent use of their respective products than a year ago ( p < .001). HTPs were perceived as less addictive than cigarettes, smokeless tobacco, and e-cigarettes, and less harmful and more socially acceptable than other tobacco products except for e-cigarettes and hookah. Conclusions: The relatively positive perceptions of HTPs and access via various channels underscores the potential penetration of HTPs among US young adults. Implications: In Fall 2019, as IQOS was launching in the US, there were relatively low rates of awareness, use, and use intentions in this sample of young adults with high proportions of other tobacco use. However, this sample reported relatively positive perceptions of HTPs with regard to potential addiction and harm, as well as social acceptability. They also reported accessing HTPs via various channels, underscoring how pervasive the availability to HTPs already has become and may increasingly become. Moreover, certain subgroups (ie, other tobacco users, men) are particularly likely to use HTPs.